2019
DOI: 10.3390/safety5020027
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Mobile Phone Use While Crossing the Road

Abstract: Phones and other portable technology can be a distraction for pedestrians, affecting their ability to cross a road safely. This study focused on adolescents and investigated whether using a phone distracts attention while crossing the road. A field observation outside a secondary school in the north of England was carried out over a four-week period in 2018 with permission from the school. Observations included recording what accessories the pedestrian was carrying (phone, headphones or another electronic devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 27 publications
(42 reference statements)
1
5
0
Order By: Relevance
“…In our study, the probability of using the phone depended on approximate age, gender and companionship, revealing higher rates of interactions with mobile devices among older children, girls and children traveling alone. Similar differences were found in previous studies on adolescents in terms of gender (Stavrinos et al, 2009) and in terms of companionship (Vollrath et al, 2019;Baswail et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our study, the probability of using the phone depended on approximate age, gender and companionship, revealing higher rates of interactions with mobile devices among older children, girls and children traveling alone. Similar differences were found in previous studies on adolescents in terms of gender (Stavrinos et al, 2009) and in terms of companionship (Vollrath et al, 2019;Baswail et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…As there is no comparable observational study in Austria, these results can only be put into relation with a survey of the Austrian Road Safety Fund, in which 34% of young people questioned stated that they listen to music while walking (Kühnelt-Leddihn et al, 2013). Other studies in Europe on young pedestrians showing rates of 25% (Vollrath et al, 2019) and 32% (Baswail et al, 2019) of holding and interacting with devices such as mobile phones or music players while crossing. It should be noted that the comparison with other studies is sometimes only possible to a limited extent due to the different characteristics of the study sites (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the Consumer Product Safety Commission of America estimated that 3.76% of American injuries are related to phone usage and Nasar et al (Nasar and Troyer, 2013a) thought injuries caused by phone usage would be much bigger. In England, a report in 2019 found that 31.37% of adolescent pedestrians crossed the crosswalks using phones (Baswail et al, 2019). Similarly, phone usage of pedestrians has been an important problem of Chinese pedestrian safety.The table 7 as well as 8 are statistics of phone usage on crosswalks in Hefei and Wuhan respectively while Fig.…”
Section: Distractionmentioning
confidence: 99%
“…Several studies have also linked adolescent risk behaviors to independence or peer influence [ 21 ]. Students’ risky travel behaviors pose a threat to their safety, including jostling on the streets, using cell phones, and riding bikes without helmets [ 22 , 23 , 24 ]. Instead of improving transportation facilities, it would be more beneficial to help young people regulate their travel behavior.…”
Section: Introductionmentioning
confidence: 99%